Peculiarities of vitamin D status in adolescent girls with non-alcoholic fatty liver disease and metabolically unhealthy obesity - E. F. Chaykivska; T. I. Kvasha; N. V. Iarotska; N. K. Silina (Publishing House TRILIST, 2020)
Non-alcoholic fatty liver disease (NAFLD) is currently the most common form of chronic liver disease, affecting 10-20% of the total pediatric population, including 8% of non-obese children and 50-80% of those who are obese. Purpose of the study was to determine the characteristics of vitamin D status in Ukrainian adolescent girls with NAFLD and metabolically unhealthy obesity. Materials and methods. 120 girls aged 12-17 years with NAFLD and metabolically unhealthy obesity, as well as 180 conditionally somatically healthy girls with normal sexual development and normal body weights (control group) were under observation. The examination set included clinical and anamnestic data, anthropometry, assessment of sexual development, clinical blood test, general urinalysis, coprogram, parasitological examination of feces, electrocardiography, lipid profile, glucose, insulin, HOMA index, alanine aminotransferase, aspartate aminotransferase, total protein, amylase, blood test for markers of hepatitis B, C, autoimmunological studies, ultrasound and elastography of the hepatobiliary system, consultation with an endocrinologist, gastroenterologist, according to the indications - cardiologist, pulmonologist, allergist and other specialists. Results. A characteristic feature of vitamin D status in adolescent girls with NAFLD and metabolically unhealthy obesity was its deficiency in 65.83% of cases, while in the control deficiency was observed less often 1.5 times - in 43.89 % of patients. The average 25(OH)D level in the group without steatosis was 22.00 ± 0.56 ng/ml, while in patients with NAFLD and metabolically unhealthy obesity it was 1.34 times lower - 16.44 ± 0.73 ng/ml. Conclusion. Correlation analysis showed the role of 25(OH)D deficiency in the development of diffuse liver diseases, disorders of lipid, carbohydrate, and purine metabolism in adolescent girls with NAFLD and obesity, that is requires an adequate correction of the status of this vitamin during treatment.